Characterization of Carbon nanotubes Near- Infrared Photoconductive Detector - Naje, Asama Natik; Abdalkrema, Ola; Hamzah, A.; M.Suhail, Abdulla (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Carbon nanotubes (MWCNTs,F-MWCNTs,SWCNTs) with different structure were fabricated into near-infrared photodetectors. Indium Tin Oxide (ITO) was used as a substrate to deposit CNTs by the drop casting method. The CNTs carrier concentrations, conductivity and carrier mobility were measured. Different types CNTs photodetectors exhibit a good photoconductive performance at a wavelength (980-1200nm) especially SWCNTs, responsivity was found to be (0.295 A W-1 ), specific detectivity (D*) 1—109 cm.Hz1/2 .W-1 and response time 0.049ns.